2020
DOI: 10.22487/preventif.v11i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Factors Relating To Safety Riding Behaviors In Students Of Senior High School 5 Palu

Abstract: Traffic accidents are still a global problem today. Traffic accidents are the main cause of death for all age groups dominated by adolescents. The number of traffic accident cases in Indonesia reached 108,871 incidents with details of which 25,511 people died. Accident data in Central Sulawesi during 2016 reached 1,889 incidents, with 420 dead, 1,076 serious injuries and 2,042 minor injuries. The city of Palu is in order no. 1 with traffic accidents 308 cases with losses of up to 616 million rupiah. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
5
Order By: Relevance
“…During the restriction of social activities, traffic accidents experienced by students were 510 (54.3%) accidents of which 50 accidents were reported to have died. The Traffic Police of Semarang City (Satlantas Polrestabes Semarang) also reported that the type of vehicle involved in traffic accidents was mostly found, that is motorcycle with a total of 73% ( 16 , 17 ). This fact supports the results of a systematic review study that there has been a change driving behavior to become more risky during COVID-19 pandemic ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the restriction of social activities, traffic accidents experienced by students were 510 (54.3%) accidents of which 50 accidents were reported to have died. The Traffic Police of Semarang City (Satlantas Polrestabes Semarang) also reported that the type of vehicle involved in traffic accidents was mostly found, that is motorcycle with a total of 73% ( 16 , 17 ). This fact supports the results of a systematic review study that there has been a change driving behavior to become more risky during COVID-19 pandemic ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The other studies mention a number of factors including the amount of exposure to driving, driving duration, social and peer factors, drugs, alcohol, and excessive speed often lead to traffic accident scenarios in adolescents ( 16 , 21 ). Meanwhile, the research in Indonesia found that having a driving license, driving attitude and behavior were factors that cause traffic accidents occurred in adolescents ( 17 ). The other studies have also found that motorcycle accidents occur due to unsafe adolescent behavior patterns, such as aggressive driving, neglect of traffic regulations, and lack of helmet use while riding ( 21 , 22 )…”
Section: Introductionmentioning
confidence: 99%
“…Pelanggaran lalu lintas merupakan keadaan yang tidak sesuai antara aturan dan pelaksanaan (Desril et al, 2018). Kemudahan untuk mendapatkan sepeda motor menjadi penyebab naiknya penggunaan sepeda motor pada remaja, khususnya usia sekolah (Salmawati & Puspita, 2020). Tindak pelanggaran yang umumnya dilakukan pelajar Sekolah Menengah Atas (SMA) atau Sekolah Menengah Kejuruan (SMK) yaitu kepemilikan SIM, penggunaan helm, kepatuhan rambu lalu lintas, kapasitas penumpang, variasi knalpot dan klakson (Desril et al, 2018;Nugroho, 2021;Salmawati & Puspita, 2020;Wulandari, Salbiah, & Seran, 2017).…”
unclassified
“…Kemudahan untuk mendapatkan sepeda motor menjadi penyebab naiknya penggunaan sepeda motor pada remaja, khususnya usia sekolah (Salmawati & Puspita, 2020). Tindak pelanggaran yang umumnya dilakukan pelajar Sekolah Menengah Atas (SMA) atau Sekolah Menengah Kejuruan (SMK) yaitu kepemilikan SIM, penggunaan helm, kepatuhan rambu lalu lintas, kapasitas penumpang, variasi knalpot dan klakson (Desril et al, 2018;Nugroho, 2021;Salmawati & Puspita, 2020;Wulandari, Salbiah, & Seran, 2017). Fenomena pengemudi pelajar yang belum layak di jalan membuat pengguna jalan lainnya merasa terganggu, terutama etika berlalu lintas (Desril et al, 2018).…”
unclassified
See 1 more Smart Citation